Oral immunization with cholera DNA vaccine employing microencapsulation delivery system - Nograles, Nadine Hayudini (2013)
Cholera disease remains to be a major public health problem in areas with poor sanitation, unsafe water supplies or in cases of epidemic outbreaks. Current oral whole-cell cholera vaccines are unable to elicit long-term protection against cholera and require maintenance of cold-chain during transport. Another vaccination strategy includes delivery of genetic components of the infectious agent. Plasmids carrying gene-coding sequences for immunostimulatory antigens such as the cholera toxin B subunit (ctxB) and/or the toxin coregulated pilin A (tcpA) genes were explored in this study as DNA vaccines for cholera. Advantages of DNA vaccines include relatively low cost and chemical stability during storage. A non-viral delivery system described as microencapsulation into alginate material, a natural polysaccharide, was utilized in this study as an oral DNA delivery vehicle. The efficiency of DNA encapsulation was evaluated in vitro through characterization of the physical and behavioral properties of the microspheres. Subsequently, comparative evaluation of the in vivo immunoglobulin production after vaccination with encapsulated DNA vaccine was performed. Alginate microspheres were produced through water-in-oil (w/o) emulsification. The average size of alginate microspheres was about 46.88 ± 3.07 μm in diameter whereby significant size reduction (p=0.028) was attributed through utilization of 1.0% Span80 in the preparation. Plasmid DNA (pDNA) was encapsulated within microspheres with encapsulation efficiencies ranging from 72.9 to 74.4% and a maximum pDNA load of 6 μg for each preparation. In simulated gastrointestinal conditions, alginate microspheres demonstrated shrinkage and minimal release of pDNA in pH 1.2 while exhibiting swelling properties in pH 9.0 with consequent pDNA release about twice the pDNA amount released in acidic environment (p<0.01). As proof-of-concept studies in vivo, orally administered pDNA–loaded alginate microspheres comprising the mammalian expression vector (pVAX), designed for DNA vaccine development, carrying the GFP reporter gene was performed. pVAX–GFP loaded–alginate microspheres, at doses of 50 μg, 100 μg and 150 μg pDNA, were delivered through oral feeding needle to BALB/c mice. Tissue biodistribution, investigated through flow cytometric analysis, demonstrated GFP positive intestinal cells (<1.0%) for the 100 μg dose, a 1.3-fold higher expression as compared to 50 μg dose. Succeeding experiments were conducted with DNA vaccines using the same approach. Oral delivery of DNA vaccine loaded–microspheres were performed on BALB/c mice and New Zealand White (NZW) rabbits. Test animals and control groups were immunized with pVAX-ctxB and/or pVAX-tcpA encapsulated within alginate microspheres. The production of antibodies observed among the test animals were compared with the control groups. Stool sIgA levels or the mucosal sIgA among vaccinated mice groups (100 μg dose) showed an increase as compared to controls with an average 6.3-fold, 1.6-fold and 1.9-fold increase at day 7, 14 and 21, respectively. The response in the rabbits were lower (on average only 29% or 159% higher than controls), observed at day 21. These results demonstrate local immune responses at mucosal surfaces of the intestinal tract among vaccinated mice and rabbits. Therefore, the alginate microspheres used in this study have shown to be potential carriers for cholera DNA vaccine into the intestinal mucosa surfaces; although further improvements are needed. The overall strategy of alginate microencapsulation which served as oral DNA vaccine therapy in this study may also serve as a delivery system for other forms of antigens or biological substances through the oral route.